If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4n + 16 = -3n + -13 Reorder the terms: 16 + -4n = -3n + -13 Reorder the terms: 16 + -4n = -13 + -3n Solving 16 + -4n = -13 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 16 + -4n + 3n = -13 + -3n + 3n Combine like terms: -4n + 3n = -1n 16 + -1n = -13 + -3n + 3n Combine like terms: -3n + 3n = 0 16 + -1n = -13 + 0 16 + -1n = -13 Add '-16' to each side of the equation. 16 + -16 + -1n = -13 + -16 Combine like terms: 16 + -16 = 0 0 + -1n = -13 + -16 -1n = -13 + -16 Combine like terms: -13 + -16 = -29 -1n = -29 Divide each side by '-1'. n = 29 Simplifying n = 29
| 100b^3-36v=0 | | 9y-7=4y+3 | | 2x-15=11x-68 | | 60h-45h=-1200+1800 | | -5+14=16x-4-15x | | x*15+28=x*5+328 | | 5x=7/3 | | x*5+28=x*5+328 | | 49x^264=0 | | 16x^2+72xy+81y^2=0 | | 1.28v+1.77v+1.34=1.79 | | (1/240)+(1/x)=(1/144) | | 30x^2+38x+12=0 | | 3(7x-2)=22x | | (3+2n)/7=5 | | .3333333t-.66666666=3 | | 8b^2-9b+1= | | 4(2c-1)-3=4c+5 | | 2-c=20 | | 50x^2-60x+18=0 | | -9(t+6)=27 | | 4(4c-1)-6=12c+2 | | 12x^2-60x+75=0 | | (x-2)/8=0.75 | | 34-18=4(x-4) | | 4x^2-9x+6=0 | | x+21+4x=-22-4x-29 | | f(x)=7xsquared-4x | | 6b^2-11bw-35w^2= | | (3/2x+20)+2x=90 | | 6t^2-14t-12=0 | | (7.1+3.5)x=45.9+x |